세치제에 함유된 비효소계 항산화제의 경시변화에 따른 잔류량 - 박정은; Jung-eun Park; 박용덕; Yong-duk Park; 홍태기; Tae-gi Hong; 장종화; Jong-hwa Jang (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of this study is to evaluate the non-enzymatic antioxidants stabilities in dentifrices by ascorbic acid and tocopherol according to the chemical condition. Methods: For the analysis of two antioxidants, HPLC UV detector system was used. HPLC was performed using sodium sulfate, acetonitrile(ACN), methanol(MeOH) and measuring absorbance at 240-295 nm. To confirm general pH reaction of two compounds, buffer solution was prepared for the analysis. The dentifrice was titrated by pH so as to examine the change of elapsed time in dentifrice. Linearity of calibration curve of two antioxidants was measured. Results: Each compound showed good linearity at optimized wavelength as well as showing good precision. General pH reaction of two antioxidants was examined. Ascorbic acid showed the highest residue(63.23%) at pH 10 and the lowest residue(2.77%) at pH 4. Tocopherol showed the highest residue(55.70%) at pH 7 and the lowest residue(3.31%) at pH 4. As a result of changing elapsed time of antioxidants in dentifrice by pH, components were remained stably at low temperature(39.2℉) and pH 7. Conclusions: It is necessary to keep dentifrice including ascorbic acid and tocopherol, and non-enzymatic antioxidants at pH 7 and low temperature for improving chemical stability.